DESIGNING VIDEO MAPPING AS PROMOTIONAL MEDIA FOR TRADITIONAL VILLAGES - I Nyoman Yoga Sumadewa; Widia Febriana; Hasbullah (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2024)
Indonesian culture is in danger of disappearing over time. Nowadays people are deceived by modern life and begin to forget the values inherited from their ancestors. Through this work, it is hoped that it will be able to arouse the enthusiasm and cohesiveness of the dancers, so that their performance can attract tourists to enjoy the Maresi dance ritual. Through this work, it is hoped that it will be able to arouse the enthusiasm and cohesiveness of the dancers, so that their performance can attract tourists to enjoy the Maresi dance ritual.Maresi Dance is a cultural heritage that is very interesting if observed and used as a source of ideas for creating Video Mapping works, moreover Maresi Dance is a traditional dance from the village of Tenganan Karangasem. Video is the most dynamic and effective source or media in conveying information. This work is intended to be able to promote Tenganan village to the wider community, so that more tourists visit Tenganan village to enjoy Maresi Dance performances and it is hoped that the existence of the dance can be maintained, adaptation to the times is needed, to be able to maintain the existence and taksu of the dance Video Mapping.